Le pilier hermaïque, une figure de passeur ? - Benjamin Perriello; Gaëlle Pivoteau-Deschodt; Vasiliki Zachari (Cahiers Mondes Anciens)
This paper analyzes a series of Hellenistic tombstones from Asia Minor and Delos which includes a herm in the scene. The meaning of the herm in such a context is unclear: although Hermes’ traditional role of voyager (particularly to the underworld) is well known, this passage is only one of many evoked by the presence of a herm on a funerary stele. We would like to underline several ways in which the herm evokes the different kinds of passage implicit in a funerary relief. The herm is connected to several levels of passage, including those which define in part the social identity of the deceased.